Literasi Visual Sebagai Dasar Pemaknaan Karya Audio Visual - Pratiwi, Sri; Balya, Tonna; Prabudi, Reza (JURNAL SIMBOLIKA: Research and Learning in Communication Study, 2019)
The general goal to be achieved in this research is to understand the ability of creators to decipher meanings (interpret) and encode (make) visuals from audio-visual works in the form of a film titled "Mauliate" which elevates the local culture of Toba. The method used in this study is a qualitative method with content analysis techniques (content analysis). The results of this study state that; the ability of creators in deciphering meanings (interpreting) and encoding (making) visuals from audio-visual works in the form of films titled "Mauliate" is still very low, because almost entirely the Batak Toba culture that is about to be portrayed does not fit the original culture both in terms of language structure, artistic representation of the Toba Batak culture, and etc.